Cost Accountability In The Manggarai Traditional House Building - Marselina, Apriana; Ismail, Nuraini; Jeradu, Vincent (SEIKO : Journal of Management & Business, 2024)
The research aims to determine the distribution system and the amount of costs incurred in the construction of the Wesa Traditional House (Mbaru Gendang), as well as to find out the implementation of accountability for the construction of the Wesa traditional house (Mbaru Gendang). The method used is descriptive qualitative research. The research location is in Ling Village, North Satar Mese District, Manggarai Regency, East Nusa Tenggara Province. Data collection techniques are observation, interviews, documentation and literature study. The research results show that the cost sharing system for building the Wesa traditional house (Mbaru Gendang) is divided into two systems, namely mandatory contributions and non-obligatory contributions (spontaneity). Contributions collected are in the form of money with a total contribution income of IDR 243,635,000.00, apart from that, also in the form of goods and involvement in development. The costs incurred in building a traditional house are divided into 2 based on the object being financed, namely direct costs related to the physical construction of the Wesa traditional house (mbaru gendang) and indirect costs related to traditional events, with a total cost of IDR 243,635,000.00 . Keywords: Cost Accountability; Construction of Traditional Houses; Mbaru Gendang Wesa.